PERBEDAAN PANDANGAN MAHASISWA UNIVERSITAS ARS DALAM MENGGUNAKAN GOOGLE MEET SEBAGAI MEDIA PEMBELAJARAN ONLINE DI MASA PANDEMI COVID-19 - Dian Rustandi; Gartika Rahmasari (Linimasa : Jurnal Ilmu Komunikasi, 2022)
At the time of the Covid-19 pandemic, educational institutions in Indonesia still use online learning using Google Meet media. Students are required to learn from home to break the chain of spread of Covid-19. Therefore, the purpose of this study is to find out the perception of ARS University students in using Google Meet media during online learning in the second year of Covid-19. This study uses phenomenological research methods with qualitative approaches to get information on the perception of students at ARS University about Google Meet during online learning in the second year of Covid-19. The selection of informants uses purposive sampling and data retrieval techniques using online interviews through google form and whatsapp communication media. The results of this study showed differences in views on each informant based on the informant's experience using Google Meet. Differences in views in using Google Meet, namely as many as 33% of informants stated more efficient and not efficient with network factors that are not good. The results also showed that using Google Meet was more flexible and some informants felt confusion when first using Google Meet, especially for new students who did online learning. There are also students who already understand the media of Google Meet so as not to feel confused. However, over time students can adjust to the use of Google Meet media to do online learning from home.